Attaining air stability in high performing n-type phthalocyanine based organic semiconductors. Issue 31 (26th July 2021) - Yutronkie, Nathan J.; King, Benjamin; Melville, Owen A.; Lessard, Benoît H.; Brusso, Jaclyn L.
Abstract : The synthesis and characterization of perfluorinated silicon phthalocyanine (F2 -F16 SiPc ) is described. OTFT device fabrication places F2 -F16 SiPc as a new benchmark for n-type MPcs and the first air-stable n-type SiPc semiconductor ever reported. Abstract : The perfluorinated analogue of silicon phthalocyanine (F2 -F16 SiPc ) has been synthesized as a novel air-stable n-type organic semiconductor. The design of F2 -F16 SiPc facilitates strong electron conduction through peripheral fluorination that deepens molecular orbital energies, while contributing to an extensive network of π⋯π′ and F⋯F′ interactions that promote a highly symmetric three-dimensional assembly as determined via single-crystal X-ray diffraction. When incorporated into organic thin-film transistors (OTFTs), electron mobilities for F2 -F16 SiPc -based devices reached performances on par with current benchmark phthalocyanine-based devices under inert environments (up to 0.30 cm 2 V −1 s −1 ), while surpassing performances under atmospheric conditions (up to 0.17 cm 2 V −1 s −1 ). These observations highlight the impact molecular and crystallographic engineering has in the development of organic-based electronics, as the F2 -F16 SiPc building block lays new grounds for the development of air-stable n-type OTFTs.